Latif Hllamt's Text "The Operate of Wolf Changes" In The Light of Deconstruction Approach (Raparin Journal of Humanities (RJH), 2020)
Deconstruction is a critical approach which was appeared after Construction approach. Deconstruction is an approach to understanding the relationship between text and meaning. Jacques Derrida is known as the father of Deconstruction.The title of the study is Latif Hllamt's text "The operate of wolf changes" in the light of Deconstruction approach.This research is a scientific attempt to analyses a specific part of Latif Hallmat's text in terms of Deconstruction. As long as the text is too long we have taken a part of the text to deal with.The research contains three sections. The first section is the definition the term of Deconstruction. The second section is about the history and philosophy of Deconstruction. The third section is about the application of the approach. At the end some conclusions and list of references are presented.